2022
DOI: 10.1021/acs.chemrev.1c00980
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of Luminescent Guests in Metal–Organic Frameworks: Understanding Pathways from Synthesis and Multimodal Characterization to Potential Applications of LG@MOF Systems

Abstract: This review gives an authoritative, critical, and accessible overview of an emergent class of fluorescent materials termed "LG@MOF", engineered from the nanoscale confinement of luminescent guests (LG) in a metal−organic framework (MOF) host, realizing a myriad of unconventional materials with fascinating photophysical and photochemical properties. We begin by summarizing the synthetic methodologies and design guidelines for representative LG@MOF systems, where the major types of fluorescent guest encompass or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
138
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 173 publications
(139 citation statements)
references
References 267 publications
0
138
0
1
Order By: Relevance
“…[113][114][115] Dye encapsulated in MOFs is an efficient method to restore the emission properties of dyes in the solid-state because of restricted aggregation caused quenching (ACQ) of the dyes by a confinement effect inside the pores of the MOFs. 116 Such dye@MOF composites thus have been used efficiently for generation of pure white light with a high quantum efficiency and CRI. A list of some common dyes which have been encapsulated in MOF structures for various opto-electronic applications including WLE is given in Fig.…”
Section: Photoluminescent Mofs (Pl-mofs) As Ree-free Phosphorsmentioning
confidence: 99%
“…[113][114][115] Dye encapsulated in MOFs is an efficient method to restore the emission properties of dyes in the solid-state because of restricted aggregation caused quenching (ACQ) of the dyes by a confinement effect inside the pores of the MOFs. 116 Such dye@MOF composites thus have been used efficiently for generation of pure white light with a high quantum efficiency and CRI. A list of some common dyes which have been encapsulated in MOF structures for various opto-electronic applications including WLE is given in Fig.…”
Section: Photoluminescent Mofs (Pl-mofs) As Ree-free Phosphorsmentioning
confidence: 99%
“…0.2-3 nm), LMOFs can be fabricated by encapsulation of a variety of luminescent guests (such as organic dyes, metal ions, metal complexes, metal nanoclusters, quantum dots, and hybrid perovskites), which usually provides certain advantages over traditional syntheses of luminescent materials. 31 For example this method broadens the light-harvesting region then enhancing the photoelectric performance, realizes multicolor fluorescence/phosphorescence emission, and minimizes the aggregation-caused quenching (ACQ) phenomena via confinement of dye guests into the pores of the crystalline MOF host. 32 However, to date, despite the promising results recently obtained on the photophysical properties of Guest@MOF, obtaining precise crystallographic information of guests encapsulated into the MOF host still remains a huge challenge.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] More studies on the relationship between the spatial positioning of guests, host-guest or guest-guest interactions, energy/ charge transport (Scheme 1) and photoelectric properties need to be carried out. 31,36 In this paper, we select the 5-ethoxyisophthalat acid (EtOIPA) ligand as the building block and acridine (AD) as the template to construct a new type of MOF host-guest system. Our previous works demonstrated that iso-phthalic acid (IPA) derivatives with bulk steric hindrance substituents at the 5-position favor the formation of metal clusters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the turn-off type sensing by fluorescence quenching has its own advantages, 9 such as the ease of practical implementations, 2 this approach poses two major limitations which are worth addressing. The first is that the side effects of environmental interference cannot be efficiently ruled out.…”
mentioning
confidence: 99%